2017
DOI: 10.5941/myco.2017.45.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Biosorption from Aqueous Solution by Endophytic Drechslera hawaiiensis of Morus alba L. Derived from Heavy Metals Habitats

Abstract: The ability of dead cells of endophytic Drechslera hawaiiensis of Morus alba L. grown in heavy metals habitats for bioremoval of cadmium (Cd2+), copper (Cu2+), and lead (Pb2+) in aqueous solution was evaluated under different conditions. Whereas the highest extent of Cd2+ and Cu2+ removal and uptake occurred at pH 8 as well as Pb2+ occurred at neutral pH (6–7) after equilibrium time 10 min. Initial concentration 30 mg/L of Cd2+ for 10 min contact time and 50 to 90 mg/L of Pb2+ and Cu2+ supported the highest bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 14 publications
3
38
0
Order By: Relevance
“…These results concur with the results of Shantha and Poonkothai who mentioned that biosorption is analogous to an ion exchange process and thus, pH of solution effects the nature of biomass binding sites and metal solubility and corroborative Rhizopus species to absorb the Ni 2+ over a extensive range of pH but the maximum uptake of Ni 2+ was found to occur at pH 6 [19]. The decrease in removal of Ni 2+ above pH 6 is because of the creation of Ni(OH) 2 . Effect of incubation time on Ni 2+ removal by both strains under study was in line with those obtained by Shantha and Poonkothai on Ni 2+ removal by Rhizopus species in which the degree of Ni 2+ uptake from the effluent by Rhizopus species exhibited a gradual increase with increasing incubation time to a point [19].…”
Section: Influence Of Various Ph On Ni 2+ Removal and Uptakesupporting
confidence: 78%
See 4 more Smart Citations
“…These results concur with the results of Shantha and Poonkothai who mentioned that biosorption is analogous to an ion exchange process and thus, pH of solution effects the nature of biomass binding sites and metal solubility and corroborative Rhizopus species to absorb the Ni 2+ over a extensive range of pH but the maximum uptake of Ni 2+ was found to occur at pH 6 [19]. The decrease in removal of Ni 2+ above pH 6 is because of the creation of Ni(OH) 2 . Effect of incubation time on Ni 2+ removal by both strains under study was in line with those obtained by Shantha and Poonkothai on Ni 2+ removal by Rhizopus species in which the degree of Ni 2+ uptake from the effluent by Rhizopus species exhibited a gradual increase with increasing incubation time to a point [19].…”
Section: Influence Of Various Ph On Ni 2+ Removal and Uptakesupporting
confidence: 78%
“…On the other side, A. terreus AHM21696 at 50 ppm Ni 2+ was totally removed after treatment for 24 h and at 100 ppm Ni 2+ was reduced by 99.65 and 100 after 2 and 4 h of treatments, respectively but 100 % Ni 2+ removal was observed at Ni 2+ concentrations of 150 ppm and 200 ppm (Table 4). Greater premier concentration affords improved leading impose to overcome all mass transmit tolerance of metal ions between the aqueous and solid phase, resulting in greater probability of collision between metal ions and sorbents [1,2]. In agreement with our results Shantha and Poonkothai suggested that the effectiveness of Ni 2+ uptake by Rhizopus species was evaluated after 7 days of fungal species inoculation in graded concentrations (25%, 50%, 75% and 100%) of the Ni 2+ electroplating effluent [19].…”
supporting
confidence: 79%
See 3 more Smart Citations